Learning and Intelligent Optimization - Maniezzo, Vittorio (Springer, 2017)
This book constitutes the thoroughly refereed post-conference proceedings of the Second International Conference on Learning and Intelligent Optimization, LION 2007 II, held in Trento, Italy, in December 2007.